The relationship between the anxiety level of people living with HIV/AIDS (PLWHA) about covid-19 and covid-19 vaccination compliance - Afritayeni, Afritayeni; Rustam, Musfardi; Maysanda, Indri Yani; Hasanah Rustam, Martha (Community Research of Epidemiology (CORE), 2023)
HIV is a type of virus that infects white blood cells causing a decrease in human immunity. The incidence of HIV in Indonesia is 50,282 people and AIDS is 7,036 people. HIV and AIDS cases have increased, from 2018-2019 HIV numbered 219 people to 249 people and AIDS numbered 226 people to 354 people. The aim of the researchers was to find out the anxiety of PLWHA during the Covid-19 pandemic with the compliance of PLWHA taking the Covid-19 vaccination. This type of quantitative research with a cross sectional approach. Total population of 152 people, using the Slovin formula obtained 61 samples, determined using accidental sampling technique. Data collection using a questionnaire. The results of the study The majority of respondents were anxious about Covid-19 in the No anxiety/mild category, namely 32 people (52.5%). And a minority of respondents experienced moderate/severe anxiety with a total of 29 people (47.5%) during the Covid-19 pandemic . The results of the chi square test obtained a significant relationship between the anxiety of PLWHA on covid-19 and the compliance of PLWHA following the covid-19 vaccination p value = 0.00 ≤ 0.05 then Ha is accepted. The implications of this research are expected to reduce the anxiety of PLWHA about COVID-19 so that they comply with the COVID-19 vaccination